2008
DOI: 10.4049/jimmunol.181.7.4570
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-1 Promotes Immunoglobulin Production during Plasma Cell Differentiation

Abstract: Galectin-1, a β-galactoside-binding soluble lectin, has been implicated in regulating immune system homeostasis. We investigated the function of galectin-1 in plasma cell differentiation and found that it is induced in primary murine and human differentiating B cells. B lymphocyte-induced maturation protein-1 (Blimp-1), a master regulator for plasma cell differentiation, was necessary and sufficient to induce galectin-1 expression. Notably, ectopic expression of galectin-1 in mature B cells increased Ig μ-chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
51
1
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 50 publications
7
51
1
3
Order By: Relevance
“…Our previous study demonstrated that Gal-1 is induced during the differentiation of mature B cells into Ig-secreting plasma cells, and this effect depends on the induction of B lymphocyte-induced maturation protein-1 (Blimp-1), the master regulator of plasma cell differentiation. We also showed that the induction of Gal-1 promotes the synthesis of Ig m-chain transcripts and the production of Ig (9). Gal-3 is required for memory B cell fate in a Schistosoma-infected animal model (10); accordingly, Gal-3 prevents the differentiation of B1 cells into IgM-secreting plasma cells (11).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Our previous study demonstrated that Gal-1 is induced during the differentiation of mature B cells into Ig-secreting plasma cells, and this effect depends on the induction of B lymphocyte-induced maturation protein-1 (Blimp-1), the master regulator of plasma cell differentiation. We also showed that the induction of Gal-1 promotes the synthesis of Ig m-chain transcripts and the production of Ig (9). Gal-3 is required for memory B cell fate in a Schistosoma-infected animal model (10); accordingly, Gal-3 prevents the differentiation of B1 cells into IgM-secreting plasma cells (11).…”
mentioning
confidence: 96%
“…Purified splenic B cells (purity .95%) were cultured, as described (18), and were stimulated with LPS (Sigma-Aldrich). The 293T, 3T3, and 293F cells were maintained, as described (9). All chemicals were purchased from Sigma-Aldrich, unless otherwise indicated.…”
Section: Cell Lines and Reagentsmentioning
confidence: 99%
“…Разнонаправленное действие галек-тина-1 на отдельные субпопуляции хелперных Т-лимфоцитов объясняется тем, что Тh1-и Тh17-дифференцированные клетки экспрессируют Галектин-1: роль в формировании 2012, Т. 14, № 1-2 набор поверхностных гликанов, ответственных за связывание галектина-1, а Тh2-клетки за счет α2-6 сиалилирования гликопротеинов клеточной поверхности устойчивы к действию данного лек-тина [64].…”
Section: Cd8unclassified
“…На различных экс-периментальных моделях показана способность галектина-1 подавлять аутоиммунную реакцию. Так, генная или белковая доставка данного лекти-на снижает клинические и гистопатологические признаки воспаления при экспериментальной аутоиммунной миастении Гравис, эксперимен-тальном аутоиммунном энцефаломиелите (EAE), коллаген-индуцированном артрите, конконава-лин А-индуцированном гепатите, воспалитель-ном заболевании кишечника, болезни транс-плантат против хозяина, экспериментальном аутоиммунном увеите, а также эксперименталь-ном и спонтанном диабете [3,28,39,42,43,52,53,63,64]. В связи с этим, галектин-1 рассма-тривается в качестве возможного агента для по-давления аутоиммунной реакции, и исследовате-лей в этой области интересует вопрос о действии галектина-1 на CD4 + Т-лимфоциты в условиях in vivo.…”
Section: Cd8unclassified
See 1 more Smart Citation